Indicadores antropométricos e marcadores de função renal em adultos e idosos - Amador, Victoria Araujo Ganzaroli (2014)
Weight excess is one of the risk factors of chronic kidney disease, so it is important to evaluate the nutritional status of population with renal function markers to monitor and prevent the increase of renal failure. The aims of this study was to evaluate the association of nutritional status indicators and renal function markers in adults and seniors. It is a cross-sectional study with 279 adults and seniors assisted by eight primary healthcare units from east Goiânia. Data were collected utilizing a standard questionnaire which included sociodemographic, life style and clinical information. Body mass index and waist circumference were taken for nutritional status evaluation; chronic kidney disease was defined as an glomerular filtration rate of less than 60 mL/min/1,73m²; microalbuminury were considerated with albumin/creatinine ratio righer than 30mg/g.Chronic kidney disease was prevalent in 8.9% and microalbuminuria in 34.8%. The prevalence of overweight was 57%. Waist circumference and body mass index had a positive association with the glomerular filtration rate, characterized as glomerular hyperfiltration. Microalbuminuria had a positive association with body mass index in women. There were a high prevalence of chronic kidney disease and overweight in the studied population. The overweight had a positive association with the glomerular filtration rate. Body mass index should be often used as it is a cheap and efficient anthropometric measurement method and is an early detection indicator of renal function in population